Jovens do campo baiano : o lugar da escolarização e do trabalho nas trajetórias e projetos de futuro - Queiroz, Sicleide Gonçalves (2011)
This study resulted from the need to broaden the investigation about the youth of the Brazilian countryside, especially in the Northeast, focusing the debate on the real conditions faced by these individuals for schooling and work in achieving its future projects. We assume that the hard working conditions in the field have led the rural youth to seek chances of survival in the city. This reality has contributed to the centralization of the work in the lives of young people, and as a result we notice schooling is put in second place as a life project, reflecting directly on school dropout. In this perspective, leaving the field does not always happen by choice, often for lack of material conditions for the stay, and in this context, the city is seen as a possibility to search for better conditions for survival through the sales force work, often in precarious conditions and overexploitation. Therefore, the question arises: What is the place of schooling and work in life projects of youngsters from Alecrim, Entrada, Massapê and Pau D‟arco,(peasant communities in the municipality of Teofilândia, in the state of Bahia, Brazil)? The survey was conducted with seventeen young, migratory experiences and non-migratory, their respective communities in order to analyze which is the place of education and labor in these individuals' lives, trying to identify the relationships established between these axes to the front prospects that involve staying in the countryside and migrating to the city. The data generated through semi-structured interview, lead to confirmation of the hypothesis that the inability to combine work with schooling has led to leaving school over the immediate need of personal survival and / or family, especially among young male. Furthermore, the data show the existence of a differentiation between the roles assigned place of schooling and work in the lives of young people and affective relationships with place and people who live in it, considered as a strong reason for the desire to stay, but insufficient to ensure the permanence of young people in the field considering the apparent lack of public policies in the communities where they live.